(3eSfO GHf GdLYOs - (3CHh GdMSf Ydj Hf GdLYO Hf YHjO GdLhgQj GdHZOGOj, GHf GdLYO,J (B230 (3g` s ((3GdMGaX eMH GdOjf GHf GdfLGQ s)
(3ChdgG (B:s
(3JHJOF HCNHGQ SYO Hf EHQGgje GHf YHO GdQMef Hf Yha s
(3BNQgG (B:s
(3hJfJgi HCNHGQ TQjc Hf YHO Gddg GdfNYi s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B269s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B100 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs